Field Testing of a Smart Geomat Based on Fiber Optic Sensors and Sensor Fusion for Levee Monitoring - Manuel Bertulessi; Francesca Ceccato; Francesco Ioli; Federico Barbieri; Livio Pinto; Paolo Simonini; Giovanni Menduni (Journal of Flood Risk Management)
ABSTRACT Real‐time monitoring of the functionality of river embankments, especially during flood events, is an increasingly important topic in the new scenario outlined by climate change. To address this issue, the concept of the “smart levee” has recently emerged, based on the fusion of information from different types of sensors to obtain, remotely and in real time, an improved knowledge of its structural health status. The work here presented applies this concept by proposing an innovative monitoring solution consisting of an anti‐erosion reinforced geomat equipped with Fiber Optic Sensors. This “smart revetment” aims to detect any surface displacement induced by failure mechanisms such as erosion and piping phenomena, as well as any physical change in soil properties (e.g., temperature and water content). These measurements, once integrated with other environmental variables, can then be associated with the variability of the most common environmental and operational factors, such as the rise in river levels during high flow events, or used to detect anomalies in the original geometry of the embankment surface. Four prototypes of this smart revetment were installed on a real levee by the city of Modena (Italy) in March 2023. The results obtained after 1 year of operation provided positive feedback on the smart revetment concept, which proved to be an innovative technological tool to improve flood resilience, both by increasing the efficiency of maintenance planning and by supporting civil protection surveillance during flood events.